The Effectiveness of Posyandu Cempaka Program in The Context of Handling Stunting in The Village of Tambak Kalisogo - Sholikah, Rifatus; Rodiyah, Isnaini (Department of Public Administration, 2023)
This research aims to analyze and describe the effectiveness of the Cempaka Posyandu Program in reducing stunting. The informants in this research were the Village Midwife, Posyandu Cadres and Village Community. The technique for determining informants used in this research is purposive sampling, namely the technique of selecting informants or sources who have certain objectives in accordance with the research theme because these people are considered to have the information needed for the research. This research uses a qualitative descriptive method with data collection techniques using interviews, observation and documentation. The data analysis model used in this research is interactive from Miles Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this research show that the effectiveness of the toddler posyandu program seen from indicators according to the Target Accuracy indicator shows that the parties who are the targets in implementing the program are not present in their entirety. The Program Socialization indicator shows that there are still many people who lack focus in receiving material or information submitted by related parties. Meanwhile, the Program Objectives indicator shows that the suitability of the initial program objectives with program implementation has not been implemented as a whole. Program monitoring shows that the program control that was carried out after the program was running was fully operational because the village midwife was assisted in its implementation and was tasked with monitoring the success of this program.